2022
DOI: 10.1177/14713012221124995
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, causes, and consequences of moral distress in healthcare providers caring for people living with dementia in long-term care during a pandemic

Abstract: Healthcare providers caring for people living with dementia may experience moral distress when faced with ethically challenging situations, such as the inability to provide care that is consistent with their values. The COVID-19 pandemic produced conditions in long-term care homes (hereafter referred to as ‘care homes’) that could potentially contribute to moral distress. We conducted an online survey to examine changes in moral distress during the pandemic, its contributing factors and correlates, and its imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Additionally, years in the profession and patient’s length of stay did not correlate with moral distress. These findings are consistent with prior lack of association with moral distress, 26 but are in contrast to other findings associated with profession, age, and years of experience. 27 Because our multidisciplinary study did not stratify by profession due to small sample size, variation across professions may not have been evident.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, years in the profession and patient’s length of stay did not correlate with moral distress. These findings are consistent with prior lack of association with moral distress, 26 but are in contrast to other findings associated with profession, age, and years of experience. 27 Because our multidisciplinary study did not stratify by profession due to small sample size, variation across professions may not have been evident.…”
Section: Discussionsupporting
confidence: 88%
“…[28] In accordance with the informants worry regarding making incorrect clinical judgements and assessments, previous research has found that dementia indeed is associated with decreased accuracy of the older patient presenting illness, [29] and that communication barriers pose risks for patients. [13,[15][16][17][18] Specifically for PLwD, whose ED visits are associated with adverse outcomes including functional decline, hospitalization, and mortality, [3,10,11,30,31] with one of the found reasons for adverse outcomes being communication barriers. [11] Indeed, PLwD are less likely to comprehend their discharge diagnosis and instructions.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Language barriers and communication barriers are known to increase the risk for patients and cause an increased work burden and moral distress for the healthcare provider. [13,[15][16][17][18] Moral distress describes the feelings of unease that arise in situations when someone knows the morally correct action to take but is constrained in some way from taking this action. It is related to malpractice, reduced quality of care, and poor communication, negatively affecting the patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residents' social isolation, hopelessness and emotional exhaustion during the pandemic were frequently reported (Palacios‐Ceña et al, 2021; Smith et al, 2023). Among staff, increased workload and shortage, high burnout and exhaustion, fears of infection, stress, anxiety, panic disorders, depression and moral distress were prevalent (Haslam‐Larmer et al, 2022; Sarabia‐Cobo et al, 2021; White et al, 2021). The pandemic also limited resident–family connectedness, which negatively affected residents' and families' psychosocial and emotional well‐being (Palacios‐Ceña et al, 2021; Pirhonen et al, 2022; Salcedo‐Pérez‐Juana et al, 2022).…”
Section: Introductionmentioning
confidence: 99%